Circulating bilirubin levels and risk of colorectal cancer: serological and Mendelian randomization analyses - Seyed Khoei, Nazlisadat; Kühn, Tilman; Katzke, Verena; Brenner, Hermann; Chang-Claude, Jenny; Hoffmeister, Michael; Weigl, Korbinian (BMC medicine, 2020)
Bilirubin, a byproduct of hemoglobin breakdown and purported anti-oxidant, is thought to be cancer preventive. We conducted complementary serological and Mendelian randomization (MR) analyses to investigate whether alterations in circulating levels of bilirubin are associated with risk of colorectal cancer (CRC). We decided a priori to perform analyses separately in men and women based on suggestive evidence that associations may differ by sex.
Gesehen am 08.02.2021